P147: Your emergency department journey: piloting a patient poster explaining the emergency department care process. (May 2019) - Krebs, L.; Villa-Roel, C.; Ushko, D.; Sandhar, G.; Ruske, H.; Couperthwaite, S.; Holroyd, B.; Ospina, M.; Rowe, B.
Abstract : Introduction : Qualitative research with emergency department (ED) patients in Alberta has revealed that some patients have limited understanding of the ED care process and that this increases the anxiety, frustration and confusion experienced throughout their visit. The objective of this study was to design, implement, and test the usefulness of a poster explaining the ED care process.Methods : As part of a stepped-wedge ED intervention trial in Alberta, a 4′ x 3′ poster portraying the patient ED care process was developed and posted in 15 study site waiting rooms. Trained research assistants approached patients in 3 urban ED waiting areas and invited them to complete a short paper-based survey on the acceptability and usefulness of the poster. Results are reported as proportions.Results : A total of 316 patients agreed to participate in this study. Approximately half of the participants were male and 60% were between the ages of 17 and 49. The majority of participants identified themselves as white (72%) and nearly half (49%) were accompanied by someone. A third (37%) of patients had read the wall poster prior to being approached to complete the survey. Most patients (62%) who had not read it prior to being approached hadn't noticed the poster or couldn't see it because of its location. Once patients reviewed the poster, the vast majority (92%) reported completely or largely understanding the information and most (84%) found it at least moderately helpful in preparing them for their ED journey. Approximately 45% of respondents agreed that they learned something new about the ED care process by reading the poster and 20% wanted additional information added to the poster; largely, wait time estimates (53% of responses).Conclusion : Placing posters in the ED is one method for equipping patients for their ED care process; however, this study revealed the potential limited utility of this engagement method by the small number of patients who noticed the poster and read the information. Location and content (e.g., time estimates) were identified as key factors for implementation. Condition-specific guides may need to supplement general ED process guides to better prepare patients for their individual ED journey and to actively engage them in their ED care.